Open science in the wild: Challenges and opportunities from Greece - Mystakopoulos, Fotis (Zenodo (CERN European Organization for Nuclear Research), 2026)
Graduation talk delivered for the Open Life Science (OLS) Nebula cohort, presenting reflections on Open Science practice in the Greek research landscape. The talk is structured around two intersecting levels of Open Science adoption. At the individual level, it considers how Open Science principles can be applied to qualitative doctoral research, including planning an "Open by Design" PhD and handling the tension between data sharing and participant privacy, a constraint qualitative interviews share with health data. At the community level, it examines how Open Science is perceived by Greek colleagues, which practices a nascent community should adopt first, and how local capacity can be aligned with international growth. The presentation closes with lessons learned across the OLS programme, including the observation that equity in Open Science is a matter of resource rather than geography alone, and that the increasing ease of producing code with large language models raises rather than lowers the need for careful attention to provenance, licensing, and citation practice. Planned next steps include developing Open Science training within Open Science Community Athens and a possible bibliographic assessment of Open Science practice adoption in Greece. Presented July 2026. The slides are also available as an accessible web version.